Effect of bypass protein on sexual behaviour of bucks - Naksar, Syamal; Nagpaul, P K; Kale, M M (The Indian Journal of Animal Sciences, 2012)
An experiment was conducted to study the effect of feeding bypass protein concentrate mixture to 20 crossbred (Alpine x Beetal) male kids from 3 months of age till maturity and to study their sexual behaviour and seminal attributes. It was revealed that bypass protein feeding had significant effect on mass activity, initial motility, live, dead and abnormality per cent of spermatozoa. The ejaculate volume, sperm concentration and total sperm count per ejaculate did not differ significantly. On the other hand, sexual behaviour traits such as the reaction time, total time taken for successful mount, protrusion score and number of unsuccessful mounts were influenced by bypass protein feeding. In all 40% animals exhibited flehman response, 53% stroke legs before mounting and 48% animals exhibited tongue flicking behaviour. It was concluded that the bypass protein feeding had significant positive impact on sexual behaviour and seminal attributes of bucks and can be recommended for feeding to animals for attaining early sexual maturity.